First, we can substitute the second equation into the first equation to eliminate x:
2(5y - 1) + 6y = -18
10y - 2 + 6y = -18
16y - 2 = -18
16y = -16
y = -1
Now that we have the value of y, we can substitute it back into the second equation to solve for x:
x = 5(-1) - 1
x = -5 - 1
x = -6
Therefore, the solution to the system of equations is (-6, -1), which corresponds to option B. (-6, -1).
Solve the system of equations.
2x+6y=−18
x=5y−1
A. (4, 1)
B. (−6, −1)
C. (−7.25, −1.25)
D. (5.25, 1.25)
1 answer